Ts. Dr. Wan Isni Sofiah develops mobile application to streamline fire extinguisher maintenance - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 11 December 2023 – While fire extinguishers are well-maintained, the absence of digitized records poses challenges for fire safety contractors in efficiently storing and accessing records. This challenge inspired Ts. Dr. Wan Isni Sofiah Wan Din, a researcher and lecturer at the Faculty of Computing (FK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), to create a Fire Extinguisher Management System (FEMS) mobile application.